2014
DOI: 10.11646/phytotaxa.181.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Cyanocohniella calida gen. et sp. nov. (Cyanobacteria: Aphanizomenonaceae) a new cyanobacterium from the thermal springs from Karlovy Vary, Czech Republic

Abstract: The thermal springs of Karlovy Vary (Carlsbad) is the locus classicus of the well-known thermal cyanobacterium Mastigocladus laminosus. In addition to the nominate variety, several other varieties and forms were described based on differences in morphology (true-branching versus non-branching) or ecology (thermal versus non-thermal). The cyanobacterial strain Kaštovský 1996/2, which was provisionally identified as M. laminosus f. nostocoides, was also isolated from this locality and discussed in previous work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
(25 reference statements)
5
35
0
1
Order By: Relevance
“…Indeed, all 16S rRNA sequences of members of Rivulariaceae sensu stricto are above 94.5% similar, suggesting that this very morphologically and ecologically diverse group could all belong to the same genus if only this criterion was used. However, previous studies demonstrated that Nostocales are highly similar in the 16S rRNA gene sequence (Flechtner et al 2002;Lukešová et al 2009;Kaštovský et al 2014) and that genera in this order frequently are more similar than 98% to at least some other genera. According to Kaštovský et al (2014), to discriminate between genus and species, the similarity threshold in the 16S rRNA gene can be very close (<99% for species, and < 98% for genera).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, all 16S rRNA sequences of members of Rivulariaceae sensu stricto are above 94.5% similar, suggesting that this very morphologically and ecologically diverse group could all belong to the same genus if only this criterion was used. However, previous studies demonstrated that Nostocales are highly similar in the 16S rRNA gene sequence (Flechtner et al 2002;Lukešová et al 2009;Kaštovský et al 2014) and that genera in this order frequently are more similar than 98% to at least some other genera. According to Kaštovský et al (2014), to discriminate between genus and species, the similarity threshold in the 16S rRNA gene can be very close (<99% for species, and < 98% for genera).…”
Section: Discussionmentioning
confidence: 91%
“…However, previous studies demonstrated that Nostocales are highly similar in the 16S rRNA gene sequence (Flechtner et al 2002;Lukešová et al 2009;Kaštovský et al 2014) and that genera in this order frequently are more similar than 98% to at least some other genera. According to Kaštovský et al (2014), to discriminate between genus and species, the similarity threshold in the 16S rRNA gene can be very close (<99% for species, and < 98% for genera). We conclude that the 16S rRNA gene sequences were too similar to serve as a reliable or sole criterion for genus or species recognition in the Rivulariaceae.…”
Section: Discussionmentioning
confidence: 91%
“…Ligation reaction was done right in the LMP gel using the Promega Easy-Vector Cloning kit (Promega Corp., Madison, WI, USA) for the Czech and Russian strains and Stratagene cloning kit for the USA strains according to the manufacturer's instructions. Five colonies were chosen at random and PCR amplified using primers T7 and SP6 and following conditions described by Kaštovský et al (2014). DNA sequencing was performed by the chain-termination method using Applied Biosystems BigDye™ Terminator Cycle Sequencing Kit v.3.1 (Life Technologies), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a number of strains assigned to Tolypothrix, Calothrix, and Microchaete have been found to form a clade within the Nostocaceae (Kaštovský & Johansen 2008, Komárek et al 2014. Strains in this clade have recurrently appeared in phylogenetic analyses without taxonomic correction, including Nostoc Fin 152, Calothrix brevissima West 1907: 180 (AB074504), Tolypothrix IAM M-259, and Nostoc PCC 7120 (Rajaniemi et al 2005, Řeháková et al 2007, Kaštovský & Johansen 2008, Lukešová et al 2009 (as "mixed Nostocaceae"), Kaštovský et al 2014). We have long recognized that this group is problematic, but it is only recently (with the description of Calochaete cimrmanii Hauer et al 2013: 38) that taxonomic revision has come to any members of this group.…”
Section: Introductionmentioning
confidence: 99%
“…Nostocaceae is among one of the most problematic group, and several genera in this family were arguably polyphyletic (Rajaniemi et al 2005a, Kozhevnikov and Kozhevnikova 2011, Zapomělová et al 2013, Komárek et al 2014, Choi et al 2018. Moreover, a number of strains assigned to Tolypothrix, Calothrix, and Microchaete have been found to form a clade within this family (Kaštovský and Johansen 2008, Kaštovský et al 2014, Komárek et al 2014). The genus Nostoc was morphologically defined as having unbranched uniseriate isopolar filaments with differentiated akinetes and terminal / intercalary heterocytes embedded in mucilaginous material-forming colonies.…”
Section: Discussionmentioning
confidence: 99%